Methods of Creating Creativity through De-familiarization Technique and the Role of the Audience in Interactive Graphics - Razieh Mokhtari Dehkordi; Azam Atapour (Budapest International Research and Critics University, 2021)
The theory of de-familiarization was first introduced in the field of literature and later due to its consistency and maturity, it was also studied in other fields and branches of art. The basis of interactive graphics is based on inviting the audience in the process of forming the work, and the de- familiarization technique can provide a platform for more creativity and interaction. The purpose of this study is to identify ways to create creativity through de-familiarization techniques and the role of the audience in interactive graphics. The question of what interactive graphics is and why they are formed is one of the issues that this research seeks to address. The main question of this article is how interactive graphics can create creative works to attract the audience through the familiarization technique? To achieve the desired goals, a qualitative research method with a descriptive-analytical nature was adopted and the studied works, which were collected through library resources, were analyzed by qualitative content analysis. The results showed that interactive graphic designers can create more creative and interactive works in the field of graphics through various methods of de- familiarization.